S1PR4 deficiency results in reduced germinal center formation but only marginally affects antibody production - Riese, Janik; Hähnel, Celine; Menz, Jonas; Hannemann, Maurice; Khabipov, Aydar; Lührs, Felix; Schulze, Tobias (Frontiers in Immunology, 2022)
Splenic B cells exhibit a high expression of the G protein-coupled sphingosine-1-phosphate (S1P) receptor type 4 (S1PR4). Little is known about the functional relevance of S1PR4 expression on those cells. In this study, S1PR4-deficient mice were used to study the role of S1PR4-mediated S1P signaling in B cell motility in vitro and for the maintenance of the splenic architecture under steady state conditions as well as in polymicrobial abdominal sepsis in vivo. Finally, the impact of S1PR4 deficiency on antibody production after immunization with T cell dependent antigens was assessed. Loss of S1PR4 resulted in minor alterations of the splenic architecture concerning the presence of B cell follicles. After sepsis induction, the germinal center response was severely impaired in S1PR4-deficient animals. Splenic B cells showed reduced motility in the absence of S1PR4. However, titres of specific antibodies showed only minor reductions in S1PR4-deficient animals. These observations suggest that S1P signaling mediated by S1PR4 modifies chemokine-induced splenic B cell chemotaxis, thus modulating splenic microarchitecture, GC formation and T cell dependent antibody production.